Effect of COVID-19 PPKM on BMI, Glucose Levels, and HbA1c in Patients DM Type 2 di Demak Regency - Kamisih, Kamisih; Azam, Mahalul; Yuniastuti, Ari (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Implementing COVID-19 Community Activity Restrictions (Pemberlakuan Pembatasan Kegiatan Masyarakat/PPKM) affects community activities, including type-2 Diabetes mellitus patients in Demak Regency. BMI and HbA1c are risk factors for increased blood glucose levels of DM type 2. This research aims to determine the impact of corvid-19 PPKM against BMI, Glucose Levels, and HbA1c in Type 2 DM Patients in Demak Regency. This study used secondary data from the Chronic Disease Management Program (PROLANIS) in three health centers (Pusat Kesehatan Masyarakat/Puskesmas) in Demak Regency. Which was grouped into measurements before PPKM (October 2019 and February 2020), the PPKM period (August 2021), and the end of PPKM (March 2022). The complete variables were incorporated into the final analysis. A total of 164 respondents were spread across in Wonosalam 1 (n=64), Bonang 2 (n=49), and Wedung 1 (n=51).  The results of the Analysis of Friedman and the Wilcoxon post hoc showed that there was an influence of COVID-19 PPKM on Glucose Levels (p= 0.000) and HbA1c (p = 0.000). There was no influence on BMI (p = 0.108) in Dm Type 2 patients in Demak Regency, meaning on the variable levels of FBS and HbA1c, there are at least two different measurements in October 2019, February 2020, August 2021, and March 2022 measurements.  Special attention is needed in DM patients to control changes in BMI, Glucose levels, and HbA1c during the implementation of COVID-19 PPKM.